ANALISIS PENGARUH FOREIGN INFLOW, INFLASI, SUKU BUNGA DAN KURS PADA RETURN SAHAM (Studi kasus pada sektor keuangan periode Juli 2016 – Januari 2017) - Bobbi, Bobbi; Haryanto, A. Mulyo (Diponegoro Journal of Management, 2017)
Flow of investment into the stock market as the impact of tax amnesty program led to the foreign markets are also feeling the impact. This study aimed to examine the effect of foreign inflow, inflation rate, interest rate and exchange rate to stock return on finance sector in tax amnesty period. Net buy is used as a proxy for the foreign inflow in stock market, interpolation of inflation rate is used for inflation, interpolation of BI 7-day repo rate is used for interest rate and exchange rate of IDR/USD is used for exchange rate.This study uses finance index in Indonesian Stock Exchange during the period July 2016 – January 2017 as the sample. The analysis technique used is regression analysis using computer software programs such as SPSS 22.0. The results showed that Foreign Inflow have significant positive effect on stock return, while Inflation, interest rate and exchange rate have no significant effect on stock return. Based on the test results of the coefficient of determination R2, the independent variables in this study had the effect as much as 31.7% to stock return.